PENGARUH PERENCANAAN INOVASI SISTEM PELAYANAN ADMINISTRASI KEPENDUDUKAN BERSAMA KANTOR POS (SIMPELPOS) TERHADAP EFEKTIVITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PANDEGLANG - marsalino marsel; Wahyu Firmansyah Hidayat (NIAGARA Scientific Journal, 2023)
In a pandemic disease virus corona 19 (Covid 19) administration service should run for people which need service, on the other side protocol Covid 19 prevention should also be implemented.As a form of innovation in the pandemic Covid 19 it is system Programs Administration Service With The post Office (SIMPELPOS), residential services in a pandemic corona viruses to simplify administrative document to the people, in addition to the efficient use of time, the cost and the certainty of completion of administrative document to be acceptable to the public then, Disdukcapil district pandeglang worked with the post office pandeglang to distribute population documents to beneficiaries. With the following problem formula : 1. How Much of The Planning Of Innovation of the Administration Service System Is Affecting Post Office (SIMPELPOS) The Effectiveness Of Administrative Service At Occupational Services And Civil Logging Districts?